2002
DOI: 10.1051/ject/200234118
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Cerebral Arterial Gas Embolism

Simon Mitchell,
Des Gorman

Abstract: Bubbles are introduced to the arterial circulation in many patients undergoing cardiac surgical procedures, and some of these distribute to the cerebral vessels. Larger bubbles may arrest in cerebral arterioles, causing ischemia and neuronal injury in the downstream territory. Smaller bubbles may redistribute through the cerebral circulation, but this is not a benign event. Their passage may cause transient ischemia and cause damage to endothelium. Margination and activation of leukoctyes follows, and may caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The BBB may be disrupted because of activation and adhesion of polymorphonuclear leukocytes in the brain ( 104 ). Generation of immune mediators induced by complement and coagulation activation by bubbles can provoke resultant thromboinflammatory coagulopathies ( 32 , 35 , 44 , 104 109 ).…”
Section: Pathophysiology: the Immunothrombotic And Endothelial Respon...mentioning
confidence: 99%
See 2 more Smart Citations
“…The BBB may be disrupted because of activation and adhesion of polymorphonuclear leukocytes in the brain ( 104 ). Generation of immune mediators induced by complement and coagulation activation by bubbles can provoke resultant thromboinflammatory coagulopathies ( 32 , 35 , 44 , 104 109 ).…”
Section: Pathophysiology: the Immunothrombotic And Endothelial Respon...mentioning
confidence: 99%
“…The BBB may be disrupted because of activation and adhesion of polymorphonuclear leukocytes in the brain ( 104 ). Generation of immune mediators induced by complement and coagulation activation by bubbles can provoke resultant thromboinflammatory coagulopathies ( 32 , 35 , 44 , 104 109 ). A typical result of air embolism is the migration of air into small arteries with an average diameter range of 30–60 µm ( 2 , 52 ).…”
Section: Pathophysiology: the Immunothrombotic And Endothelial Respon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive decline is a common complication following cardiac surgery and affects approximately 26%–40% of patients [24] . Therefore, recent studies have highlighted the importance of preventing the generation of MBs and their entry into a patient's body [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It has been observed that while larger bubbles usually embolize cerebral arterioles, causing focal ischemia and neuronal injury, small emboli navigate along the vessels, provoking an insult to the endothelium and triggering an inflammatory response, microvascular dysfunction, and cognitive decline. 16–18…”
mentioning
confidence: 99%